HUBUNGAN PENGETAHUAN DAN SOSIAL BUDAYA TERHADAP MOTIVASI IBU BALITA MENGIKUTI IMUNISASI MEASLES RUBELLA - YELFITRIA YELFITRIA; ALINI ALINI; RINDA FITHRIYANA (Jurnal Ners, 2020)
Diabetes Mellitus is a degenerative disease that has increased every year in countries around the world. The prevalence of diabetes globally affects around 9% of adults aged 18 years and over in 2014. The aim of the study was to determine the factors that influence elderly adherence in taking type 2 diabetes mellitus medication in the Kuapan Village, the working area of the Puskesmas Tambang year 2019. This type of research is quantitative with a cross sectional study design. The population in this study were elderly patients suffering from type 2 diabetes mellitus in the Kuapan Village, the Puskesmas Tambang Work Area in July 2019 with a total of 57 respondents. The data analysis used was univariate and bivariate analysis with the Chi Square test. The results showed that there was a relationship between family support (p value = 0.003), length of treatment (p value = 0.001) and support from health workers (p value = 0.000) with elderly adherence in taking type 2 Diabetes Mellitus medication. increase support to patients by motivating patients, especially in taking medication, trying to meet the needs of patients in their treatment and improving communication with patients.